Test the Effectiveness of Infusion Formulation of Tamarind Fruit (Tamarindus indica) with Temu Kunci (Boesenbergia Rotunda) Rhizome against Head Lice Mortality (Pediculus Humanus Capitis): Uji Efektivitas Formulasi Infusa Buah Asam Jawa (Tamarindus indica) dengan Rimpang Temu Kunci (Boesenbergia Rotunda) terhadap Mortalitas Kutu Rambut (Pediculus Humanus Capitis) - Princella, Adelia Octa; Ardiansyah, Syahrul (Universitas Muhammadiyah Sidoarjo, 2020)
Pediculosis capitis is an infectious disease caused by the parasite infestation Pediculosis humanus capitis. It is necessary to do alternative medicine by using natural ingredients as insecticides to kill head lice, one of which is tamarind fruit (Tamarindus indica) and temu Kunci rhizome (Boesenbergia rotunda) which have chemicals that work as insecticides. The form of the research is experimental in nature at the Laboratory of Clinical Parasitology, University of Muhammadiyah Sidoarjo. The sample used was head lice obtained as many as 480 tails from santriwati Pondok Pesantren Nurul Ikhlas Sidoarjo tested with tamarind fruit and rhizome of Temu Kunci obtained from the Probolinggo area, East Java. Samples were tested with 6 treatments, namely 100% tamarind fruit; 25% tamarind and 75% meeting lock; 50% tamarind and 50% meeting lock; 75% tamarind and 25% meeting lock; 100% key retrieval; negative control (aquades) and 4 repetitions. The data obtained for 24 hours were analyzed by using the One Way ANOVA statistical test and continued with the LSD test. One Way ANOVA test obtained a significance value of P= 0.000 (p<0.005) and in the LSD further test, the most effective infusion solution was obtained at K4 (75% tamarind fruit and 25% rhizome of Temu Kunci). The conclusion is that there is an effectiveness of infusion formulation of tamarind fruit (Tamarindus indica) with temu lock rhizome (Boesenbergia rotunda) which can eradicate head lice (Pediculus humanus capitis).